Motivations for outdoor recreation in tropical urban parks - Mohamad Muslim, Huda Farhana; Abdul Kadir, Nik Azyyati; Yahya, Noor Azlin; Mamat, Mohd Parid (2017)
The modern urban environments generally limit people’s access to nature has resulting in reduced human–nature interaction.Thus, establishment of urban parks are potential resource for a diversity of urban people to interact with nature including in urban tropical cities. This article will determine individual or the park characteristics has influenced the park users’ level of satisfaction in selected five public parks including Penang Municipal Park and Taiping Lake Garden, Perak. The park users’ strongly agreed that peaceful attribute as the main attraction in urban parks (Mean = 4.21). Daily trips to the parks had reduce their stress (M= 4.42); strengthen relationships with families and friends (M = 4.20) and they felt happier (M= 4.13). The Malay, male, youth group (15 to 24 years old), single and people with lower income (< MYR 3000) were dominated in the urban parks, and many of them were universities and higher grade levels.The statistical analysis confirmed socio-demographic characteristics (age, ethnicity, and education attainment) significantly influenced the satisfaction on nature attractions. Peaceful surrounding and outdoor recreation activities in urban parks enrich urbanities psychological and social benefit (stress reduction, become happy and strengthen relationships), which positive reflect people’s well-being and quality of life.Urban people also prefer park with a variety of recreation activities instead attractive natural areas.Notably, it fulfils the needs of open spaces increment in sustainable cities for positive community transformation in social and psychological benefits